Economic Structural Change as an Option for Mitigating the Impacts of Climate Change - Golub, Alexander (World Bank, Washington, DC, 2016)
Improving the resilience of the economy in the face of uncertain climate change damages involves irreversible investments to scale up new technologies that are less vulnerable to the effects of climate change. The benefit of having such options includes the avoided welfare cost of diverting consumption to scaling up the new technology after production possibilities have been diminished by climate change impacts. This needs to be balanced against the upfront cost of scaling up a technology that is potentially less productive than incumbent technologies. The paper uses a real options approach to investigate this trade-off, based on numerical simulation of a multi-period model of economic growth and climate change impacts that includes a one-time cost associated with scaling up the alternative technology. The value of the option provided by investment in the more resilient technology depends on the ex-ante volatility of climate change damages, as well as how rapidly climate change degrades the productivity of the economy's established technology. In addition, the size of scale-up cost that leaves the economy indifferent between investing and not investing in the new technology can be used to define the value of early investment in the less climate change–vulnerable technology as a sort of call option.